Legal Certainty in Digital Spatial Planning Licensing: Rethinking Administrative Decision-Making in Urban Governance - Didi Nursidi (Sultan Publisher, 2025)
The digitalization of spatial planning permits has become an important part of urban governance reform, particularly in efforts to improve administrative efficiency and coordination. However, digitalization not only brings procedural changes but also affects how administrative decisions are made and legally accountable. This research aims to analyze digital-based spatial planning permits as an instrument of administrative law, focusing on their implications for the structure of administrative decisions, legal certainty, and administrative justice in urban governance. This research uses a qualitative approach with a juridical-normative method enriched by conceptual analysis. Research data is sourced from administrative legal norms, relevant laws and regulations regarding spatial planning and permits, as well as relevant scientific literature. The research results indicate that the digitalization of permits changes the structure of administrative decision-making from an individual-hierarchical model to a system-based integrated model, which increases procedural efficiency but simultaneously introduces new complexities in the division of legal authority and responsibility. Additionally, digitalization tends to strengthen procedural certainty, but it has not fully guaranteed substantive legal certainty and administrative justice. This research confirms that the success of digital spatial planning licensing is highly dependent on strengthening the administrative legal framework, harmonizing regulations, and establishing effective accountability mechanisms and legal protection.